Assessment of Safety Practices Among Commercial Long Distance Bus Drivers in Benin City, Edo State, Nigeria - Okafor, Kingsley Chinedu; Okogie, Obehi Hilda; Ogbogodo, Esohe Olivia (European Journal of Applied Sciences, 2023)
Introduction: Safety practices by road users are important for road safety. The actions or inactions of drivers can result in Road Traffic crashes6.To assess safety practices and related factors among commercial long distance bus drivers in Benin City, Edo State, Nigeria. Materials and Methods: A descriptive cross sectional study design was used, and data was collected from 315 commercial long distance bus drivers and their vehicles from January to October, 2015 using a structured interviewer administered questionnaires and focus group discussion guide. Respondents were recruited using systematic random sampling technique. Data was analysed using SPSS version 20. Results: Data showed that 114 (36.2%) were within the age group of 31-40 years. Most of the respondents 272 (86.3%) were married, almost all the respondents 311 (98.7%) were males, while, 4 (1.3%) were females. More than half of the respondents 172 (54.6%) had a secondary level of education, 112 (35.6%) had a primary level of education while 12 (3.8%) had no formal education. About a quarter 83 (26.3%) drive at a safe speed of 80-100 km/hour as approved by the Nigerian high way code. More than two thirds of the respondents 216 (68.6%) drive at a speed between >100-120 km/hour, while 12 (3.8%) drive above 120 km/hour. Majority of the respondents 235 (74.6%) were observed using seat belt as a safety practice while 80 (25.4%) were not using their seat belt. There was a statistically significant association between the respondents’ level of education and their use of seat belts (p = 0.002). Other safety practices done by respondents were daily vehicle checks 272 (86.3%), obeying traffic rules 284 (90.2%), Unsafe practices done by drivers include violation of road traffic signs (48.4%), violation of parking regulations (45.2%) , Use of mobile phones (48.9%), having a soft drink while driving (23.5%), putting a child on the front seat while driving (3.5%), drinking alcohol while driving (2.5%), smoking while driving (1.6%), reading newspapers while driving (0.6%). Conclusion: The common safety practice seen in commercial drivers included, use of seat belt, driving within speed limits, daily vehicle checks, obeying traffic rules, avoidance of substance use and avoidance of use of mobile phones while driving. Recommendations include encouraging drivers organizing quarterly meetings, workshops and seminars for commercial long distance drivers on safety practices during driving, prevention and control of road traffic accidents and promoting and ensuring drivers’ compliance with traffic rules.